How can we reduce costs of solid‐phase multiplex‐bead assays used to determine anti‐HLA antibodies?. (18th August 2016) - Kamburova, E. G.; Wisse, B. W.; Joosten, I.; Allebes, W. A.; van der Meer, A.; Hilbrands, L. B.; Baas, M. C.; Spierings, E.; Hack, C. E.; van Reekum, F. E.; van Zuilen, A. D.; Verhaar, M.; et al.
Abstract: Solid‐phase multiplex‐bead assays are widely used in transplantation to detect anti‐human leukocyte antigen (HLA) antibodies. These assays enable high resolution detection of low levels of HLA antibodies. However, multiplex‐bead assays are costly and yield variable measurements that limit the comparison of results between laboratories. In the context of a Dutch national Consortium study we aimed to determine the inter‐assay and inter‐machine variability of multiplex‐bead assays, and we assessed how to reduce the assay reagents costs. Fifteen sera containing a variety of HLA antibodies were used yielding in total 7092 median fluorescence intensities (MFI) values. The inter‐assay and inter‐machine mean absolute relative differences (MARD) of the screening assay were 12% and 13%, respectively. The single antigen bead (SAB) inter‐assay MARD was comparable, but showed a higher lot‐to‐lot variability. Reduction of screening assay reagents to 50% or 40% of manufacturers' recommendations resulted in MFI values comparable to 100% of the reagents, with an MARD of 12% or 14%, respectively. The MARD of the 50% and 40% SAB assay reagent reductions were 11% and 22%, respectively. From this study, we conclude that the reagents can be reliably reduced at least to 50% of manufacturers' recommendations with virtually no differences in HLA antibody assignments.